2018
DOI: 10.1016/j.susc.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A Microscopic Model of the Electrochemical Vibrational Stark Effect: Understanding VSF Spectroscopy of (bi)Sulfate on Pt(111)

Abstract: external bias. These results imply that essentially all spectroelectrochemical studies that have attributed chemical significance to changes in slope of spectral parameters with applied bias should be revisited, as potential dependent dipoledipole interaction can induce such changes independent of any structural or chemical change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…However, in practice using the bulk spectral response of either species to assign features observed when the anions are adsorbed is challenging: adsorption may break bulk anion symmetry, and alter the vibrational response due to changes in electronic structure or the presence of interfacial fields. 19,20,23,28,29 This conclusion is consistent with recent electronic structure calculations on Pt clusters, 30 and extended (periodic) Pt surfaces. 20 To complement these experiments we performed density functional theory calculations of a sulfate and bisulfate adsorbed on the Pt(111) surface of a cluster of 55 Pt atoms (see Fig.…”
Section: As Mentioned Above Sosupporting
confidence: 91%
See 2 more Smart Citations
“…However, in practice using the bulk spectral response of either species to assign features observed when the anions are adsorbed is challenging: adsorption may break bulk anion symmetry, and alter the vibrational response due to changes in electronic structure or the presence of interfacial fields. 19,20,23,28,29 This conclusion is consistent with recent electronic structure calculations on Pt clusters, 30 and extended (periodic) Pt surfaces. 20 To complement these experiments we performed density functional theory calculations of a sulfate and bisulfate adsorbed on the Pt(111) surface of a cluster of 55 Pt atoms (see Fig.…”
Section: As Mentioned Above Sosupporting
confidence: 91%
“…16,23 We have recently shown that the potential dependent changes in peak amplitude, bandwidth and frequency, for E 4 0.42 V, can be quantitatively understood as the result of interplay between the local field strength across the adsorbed layer and the potential dependent change in anion polarizability: the apparent changes in slope of spectral parameters with applied bias around 0.7 V can be understood without invoking a change in surface structure or chemistry. 19 Here we address the assignment of this peak.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The glassware was cleaned by (1) immersion in alkaline permanganate solution for 24 h (2) immersion in Piranha solution for 2 h and (3) repeated supersonication in ultrapure water. Exact details of the cleaning procedure for the glassware can be found in our previous work . All solutions were prepared from Milli‐Q water and Suprapur sulfuric acid (Merck).…”
Section: Methodsmentioning
confidence: 99%
“…Exact details of the cleaning procedure for the glassware can be found in our previous work. [41] All solutions were prepared from Milli-Q water and Suprapur sulfuric acid (Merck). The single crystalline working electrodes (5 mm diameter, 3 mm thick, MaTeck) were flame annealed in a butane air flame (for 4 × 1 min plus 1 × 15 min), cooled in water saturated N 2 , and then quenched in and covered with a droplet of N 2 purged Milli-Q water.…”
Section: Methodsmentioning
confidence: 99%